2021
DOI: 10.1002/onco.13680
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Dexamethasone for Antiemesis when Combining Chemotherapy and Immunotherapy

Abstract: Whether the immune suppressive action of glucocorticoid steroids, such as dexamethasone, might reduce the benefits of cancer immunotherapy has long been a concern. Observations that established tumor regressions in response to immune checkpoint inhibitors (ICIs) often persist, despite the use of steroids to mitigate ICI‐related autoimmune breakthrough, are not sufficiently reassuring, because these observations do not address the potential blunting of immune priming at the initiation of ICI therapy. With incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Numerous studies have reported that emodin treatment can significantly decrease the production of serum AMY and inflammatory mediators or cytokines in lung tissues (27,40). Additionally, DEX has been shown to act as a non-specific immune inhibitor (42). It was reported that its use inhibited the production of numerous inflammatory mediators and increased the synthesis of proteins associated with anti-inflammatory responses (43).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that emodin treatment can significantly decrease the production of serum AMY and inflammatory mediators or cytokines in lung tissues (27,40). Additionally, DEX has been shown to act as a non-specific immune inhibitor (42). It was reported that its use inhibited the production of numerous inflammatory mediators and increased the synthesis of proteins associated with anti-inflammatory responses (43).…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies prevent tumor immune tolerance by blocking ligand-receptor interactions and subsequent effector signaling that ultimately inhibit anti-tumor immune responses [50]. The use of ICIs has revolutionized oncology and induced substantial leaps in the treatment of a wide range of tumors including melanoma and non-small cell lung cancer (NSCLC) [51], both capable of metastasis to the brain. Several studies assessing ICI utility in brain tumors were compiled in a large systematic review and demonstrated a moderate response to ICI in melanoma and NSCLC brain metastases with some clinical effects in glioblastoma [51].…”
Section: Icismentioning
confidence: 99%
“…In cisplatin-based chemotherapy, no clear-cut conclusion can be drawn from studies currently available [ 143 , 144 ]. In patients receiving immunotherapy, the lowest effective dose of dexamethasone is recommended [ 145 ] and the lowest effective dose is also recommended for prophylaxis of CINV during the COVID-19 pandemic [ 146 ]. This is of special interest for older cancer patients, because the single-day dexamethasone strategy enables the entire antiemetic prophylaxis to be administered before chemotherapy with no need for routine antiemetics in the subsequent days, resulting in optimal compliance.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%